MEDIA UNDER THE OLD DEVELOPMENT THEORIES AND MEDIA UNDER THE POST-MODERNIST ERA - Winda Kustiawan; Arif Indra Hasan hrp; Vira Nabila; Nursadimah Berutu; Elsa jeynita Agustias; Aqilah Anisah Parkha Siregar (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2023)
Media has an important role in influencing culture and human way of life. Over the years, the media has continued to evolve with technological developments and social changes, thus having an impact on media development theories. In media history, there are two influential theories of media development, namely the old development theory and the post-modernist era. The aim of this article is to discuss old developmental theories and the post-modernist era in media development. By conducting a discussion of the introduction of the theory, the media used, the role of technology, technological change and the impact and implications of future media development so that it can become the basis for better and more effective media development in the future. In the development of the media, the theory of old developments and the Post Modernist era has a significant influence. In conclusion, media development cannot be separated from the surrounding social, technological, cultural and consumer behavior environment. Therefore, media companies and media developers should consider these factors in the development of more responsive, personalized and relevant media in the future.